(untitled) (Journal of Dhaka National Medical College & Hospital, 2026)
Background: Dementia is already a significant health and socioeconomic challenge, even in developing nations such as Bangladesh, as a result of the aging population and various associated risk factors. This study has assessed the likelihood of vitamin B12 deficiency among the elderly diabetic population in Bangladesh. Materials and Methods:The study utilized a cross-sectional observational design. After obtaining informed written consent, data collection was conducted involving 172 respondents or their caregivers through a structured questionnaire derived from the Addenbrooke’s Cognitive Examination (ACE-III) to assess cognitive status. Participants were divided into two groups based on their ACE-III score: Group I for diabetic mellitus (DM) with dementia (score ≤70) and Group II for DM without dementia (score >70). The analysis of data was conducted employing both univariate and multivariate statistical methods, as deemed suitable. Results: In this study,mean± SD of Vitamin B-12 levels showed highly significant difference (p<0.001) between groups. In this study significant positive correlation was found between ACE-III total score with Vitamin B-12 levels (ρ= 0.445; p=0.000). Also by doing multivariate analysis positive association was found between ACE-III total score with vitamin B-12 with p=0.000, 95.0% CI; 0.003 to 0.002, Odds ratio; 10.825. Conclusions: A deficiency in Vitamin B12 is associated with cognitive function and therapy to replace this vitamin might be a potential approach to enhance cognitive outcomes in patients. Additional research is required to validate and clarify the identified relationships on a broader scale and to assess whether these results will lead to a decrease in cognitive decline. J Dhaka National Med. Coll. Hos. 2025; 31 (02): 24-27